2012
DOI: 10.1111/j.1475-2743.2012.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus sorption and desorption properties of soils developed on basic rocks under a subhumid Mediterranean climate

Abstract: Representative samples of A, B and C horizons from 11 pedons (Luvisols, Solonetzs and Cambisols) developed on intermediate and basic rocks were studied regarding evaluation of phosphorus (P) behaviour, with the aim of delineating site‐specific management practices. For this purpose, (i) sorption properties were evaluated by Langmuir and Freundlich isotherms, (ii) soil samples were fertilized to a level of ca. 0.5 mg P/L, estimated by the Freundlich isotherm fitted to each horizon and (iii) the amount of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Unlike the present study, in other research conducted for Andosols ( Van Ranst et al, 2004 ; Auxtero, Madeira & Sousa, 2008 ) the best fit corresponded to Langmuir isotherms. Both the Langmuir and Freundlich models well describe P sorption on a variety of Australian soils ( Singh & Gilkes, 1991 ), Thai Oxisols and Ultisols ( Wisawapipat et al, 2009 ), soils developed from basic rocks in Portugal ( Horta et al, 2013 ), and forest and vineyard soils from Galicia, Spain ( Romar-Gasalla et al, 2016 ). The Langmuir, Freundlich and Temkin models can be used to describe P sorption on various Chinese soils ( Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the present study, in other research conducted for Andosols ( Van Ranst et al, 2004 ; Auxtero, Madeira & Sousa, 2008 ) the best fit corresponded to Langmuir isotherms. Both the Langmuir and Freundlich models well describe P sorption on a variety of Australian soils ( Singh & Gilkes, 1991 ), Thai Oxisols and Ultisols ( Wisawapipat et al, 2009 ), soils developed from basic rocks in Portugal ( Horta et al, 2013 ), and forest and vineyard soils from Galicia, Spain ( Romar-Gasalla et al, 2016 ). The Langmuir, Freundlich and Temkin models can be used to describe P sorption on various Chinese soils ( Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lower values of R 2 could be caused by the non-exhaustion of the maximum sorption capacity of the materials in the established range of contaminants. The results of phosphate removal (R 2 from 0.548 to 0.986) were described least precisely, despite the fact that numerous authors have shown the usefulness of the Langmuir isotherm for the description of phosphate sorption on minerals and organic materials [78,79]. This could be caused by the low abilities of the applied materials for the removal of such contaminants.…”
Section: Equilibrium Testsmentioning
confidence: 93%
“…Unlike the present study, in other research conducted for Andosols (Van Ranst et al, 2004;Auxtero et al, 2008) the best fit corresponded to Langmuir isotherms. Both the Langmuir and Freundlich models well describe P sorption on a variety of Australian soils (Singh and Gilkes, 1991), Thai Oxisols and Ultisols (Wisawapipat et al, 2009), soils developed from basic rocks in Portugal (Horta et al, 2013), and forest and vineyard soils from Galicia, Spain (Romar-Gasalla et al, 2016). The Langmuir, Freundlich and Temkin models can be used to describe P sorption on various Chinese soils (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%